A joint modelling framework for daily extremes of river discharge and precipitation in urban areas. Issue 1 (30th March 2015) - Breinl, K.; Strasser, U.; Bates, P.; Kienberger, S.
Abstract: Human settlements are often at risk from multiple hydro‐meteorological hazards, which include fluvial floods, short‐time extreme precipitation (leading to 'pluvial' floods) or coastal floods. In the past, considerable scientific effort has been devoted to assessing fluvial floods. Only recently have methods been developed to assess the hazard and risk originating from pluvial phenomena, whereas little effort has been dedicated to joint approaches. The aim of this study was to develop a joint modelling framework for simulating daily extremes of river discharge and precipitation in urban areas. The basic framework is based on daily observations coupled with a novel precipitation disaggregation algorithm using nearest neighbour resampling combined with the method of fragments to overcome data limitations and facilitate its transferability. The framework generates dependent time series of river discharge and urban precipitation that allow for the identification of fluvial flood days (daily peak discharge), days of extreme precipitation potentially leading to pluvial phenomena (maximum hourly precipitation) and combined fluvial–pluvial flood days (combined time series). Critical thresholds for hourly extreme precipitation were derived from insurance and fire service data.